Validation of birth outcomes from the SART CORS: Population-based analysis from the Massachusetts Outcome Study of Assisted Reproductive Technology (MOSART) - Stern, Judy E (Fertil Steril, 2016)
OBJECTIVE: To assess the validity of outcome data reported to the Society for Assisted Reproductive Technology Clinic Outcome Reporting System (SART CORS) compared to data from vital records and the birth defects registry data in Massachusetts. DESIGN: Longitudinal cohort SETTING: Registry and vital records data PARTICIPANTS: 342,035 live births and fetal deaths to Massachusetts mothers giving birth in-state from July 1, 2004 to December 31, 2008; 9,092 births and fetal deaths were to mothers who had conceived with assisted reproductive technology (ART) and whose cycle data had been reported to the SART CORS. INTERVENTIONS: None MAIN OUTCOME MEASURES: Percent agreement between maternal race and ethnicity, delivery outcome (live birth or fetal death), plurality (singleton, twin, or triplet+), delivery date, and singleton birthweight reported in the SART CORS versus vital records; sensitivity and specificity for birth defects among singletons as reported in the SART CORS versus the Massachusetts Birth Defects Monitoring Program (BDMP). RESULTS: There was >95% agreement between the SART CORS and vital records for fields of maternal race/ethnicity, live birth/fetal death, and plurality; birth outcome date was within 1 day with 94.9% agreement while birthweight was within 100 grams with 89.6% agreement. By contrast, sensitivity for report of any birth defect was 38.6% with range 18.4% to 50.0% for specific birth defect categories. CONCLUSIONS: While most SART CORS outcome fields are accurately reported, birth defects variables showed poor sensitivity when compared with the gold standard data from the BDMP. We suggest that reporting of birth defects be discontinued.